Small Molecule Inhibitors of the Host Cell COX/AREG/EGFR/ERK Pathway Attenuate Cytomegalovirus-induced Pathogenesis - Melnick, Michael (2011)
As with other herpesviruses, human cytomegalovirus (hCMV) has the ability to establish lifelong persistence and latent infection following primary exposure, salivary glands (SMGs) being the primary site of both. In the immunocompromised patient, hCMV is a common cause of opportunistic infections, and subsequent morbidity and mortality. Elucidating the molecular pathogenesis of CMV-induced disease is critical to the development of more effective and safer drug therapies. In the present study, we used a novel mouse postnatal SMG organ culture model of mCMV-induced dysplasia to investigate a candidate signaling network suggested by our prior studies (COX-2/AREG/EGFR/ERK). The objective was to employ small molecule inhibitors to target several key steps in the autocrine loop, and in this way ameliorate pathology. Our results indicate that upregulation of ERK phosphorylation is necessary for initial mCMV-induced pathogenesis, and that ErbB receptor family phosphorylation and downstream signaling are highly relevant targets for drug discovery.